Parental barriers in preventing recurrent thalassemia in children: A qualitative study - Mardhiyah, Ai; Yosep, Iyus; Rakhmawati, Windy; Fitri, Siti Yuyun Rahayu; Shalahuddin, Iwan (Universitas Aisyah Pringsewu, 2024)
Thalassemia is a genetic blood disorder that can cause a heavy burden on families, especially parents whose children suffer from this condition. Parental involvement in preventing thalassemia in children is key, but there are many challenges to be faced. The aim of this study was to explore parental barriers in preventing recurrent thalassemia in children. This research uses a qualitative design with a phenomenological approach. Researchers conducted interviews and focus group discussions with 15 parents of children with thalassemia at a hospital in West Java Province. Data was collected and then analyzed using a phenomenological approach to identify main themes. The results of the study show that the barrier for parents in preventing recurrent thalassemia is the belief that my bloodline is clean, because there are no plans to have more children, so lazy to do screening, busy time, fear, expensive cost, and desire to have another child . This study found that there are various psychosocial and economic factors that influence parents' decisions in preventing thalassemia in their children. Increased education and financial support can help reduce the barriers parents face. More inclusive health policies and social support programs designed to target these factors could improve thalassemia prevention efforts.